Five Antigen Tests for SARS-CoV-2: Virus Viability Matters - Homza, Miroslav; Zelena, Hana; Janosek, Jaroslav; Tomaskova, Hana; Jezo, Eduard; Kloudova, Alena; Mrazek, Jakub; Svagera, Zdenek; Prymula, Roman (Viruses, 2021)
Antigen testing for SARS-CoV-2 (AGT) is generally considered inferior to RT-PCR testing in terms of sensitivity. However, little is known about the infectiousness of RT-PCR positive patients who pass undetected by AGT. In a screening setting for mildly symptomatic or asymptomatic patients with high COVID-19 prevalence (30-40%), 1141 patients were tested using one of five AGTs and RT-PCR. Where the results differed, virus viability in the samples was tested on cell culture (CV-1 cells). The test battery included AGTs by JOYSBIO, Assure Tech, SD Biosensor, VivaChek Biotech and NDFOS. Sensitivities of the ATGs compared to RT-PCR ranged from 42% to 76%. The best test yielded a 76% sensitivity, 97% specificity, 92% positive, and 89% negative predictive values, respectively. However, in the best performing ATG tests, almost 90% of samples with "false negative" AGT results contained no viable virus. Corrected on the virus viability, sensitivities grew to 81-97% and, with one exception, the tests yielded high specificities >96%. Performance characteristics of the best test after adjustment were 96% sensitivity, 97% specificity, 92% positive, and 99% negative predictive values (high prevalence population). We, therefore, believe that virus viability should be considered when assessing the AGT performance. Also, our results indicate that a well-performing antigen test could in a high-prevalence setting serve as an excellent tool for identifying patients shedding viable virus. We also propose that the high proportion of RT-PCR-positive samples containing no viable virus in the group of "false negatives" of the antigen test should be further investigated with the aim of possibly preventing needless isolation of such patients.
Keywords: RT-PCR; antigen testing; antigeny virové; Sensitivity and Specificity; senzitivita a specificita; False Negative Reactions; Humans; lidé středního věku; mikrobiální viabilita; Female; dospělí; falešně negativní reakce; sérologické testy; lidé; Microbial Viability; Adult; COVID-19; ženské pohlaví; infectiousness; Male; Middle Aged; testování na COVID-19 průkazem nukleové kyseliny; COVID-19 Testing; COVID-19 Nucleic Acid Testing; Mass Screening; Antigens, Viral; Serologic Tests; testování na COVID-19; plošný screening; mužské pohlaví; SARS-CoV-2; viability